PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VIII B SMP NEGERI 1 MAESAN - Setyo Pujo Hartono (ScienceEdu: Jurnal Pendidikan IPA, 2019)
The research aims to increase the activity and learning outcomes of the human circulatory system by applying discovery learning combined with quiz games. The learning process that has not been centered on students, makes learning activities less and results in low student learning outcomes. The application of discovery learning is expected to make learning more meaningful, because it will change the passive learning conditions to be active and creative so that students can gain their own knowledge about the human circulatory system. The results showed 88.9% of students completed with an average value of 79.6. The application of discovery learning combined with quiz games has been proven to be able to increase the activity and learning outcomes of the human blood circulation system in grade VIII B students of Maesan 1 Junior High School in 2018/2019 Academic Year.